Stabilitas Fisikokimia dan Kompatibilitas Tekstur Yoghurt Susu Sapi yang Diperkaya dengan Rumput Laut Merah (Eucheuma cottonii) - Muhammad Yusuf; Reihan Azharuddiya Adzani; Diode Yonata (Universitas Muhammadiyah Semarang, 2026)
This study investigated the effect of Eucheuma cottonii incorporation on the physicochemical and textural properties of cow’s milk yoghurt. Yoghurt was produced using a one-factor experimental design with different concentrations of E. cottonii slurry added prior to fermentation. Physicochemical properties, including pH, total solids, viscosity, syneresis, and colour parameters (L*, a*, b*), were evaluated. Texture profile analysis was performed to determine hardness, adhesiveness, and cohesiveness. Data were analyzed using one-way analysis of variance and response trends were visualized using Design-Expert software. The results showed that increasing E. cottonii concentration reduced syneresis and slightly increased viscosity and total solids, indicating improved water holding capacity and structural stability of the yoghurt matrix. pH values remained within the typical range of fermented dairy products, suggesting that seaweed incorporation did not interfere with lactic acid fermentation. Texture profile analysis revealed a moderate increase in hardness, while adhesiveness and cohesiveness remained relatively stable across formulations, indicating good compatibility between seaweed-derived polysaccharides and the yoghurt gel network. Overall, the findings demonstrate that Eucheuma cottonii can be incorporated into cow’s milk yoghurt as a natural stabilizing ingredient to enhance product stability without adversely affecting texture or fermentation characteristics. This study provides insight into the potential application of red seaweed as a functional ingredient in fermented dairy products.